INTERCULTURAL COMMUNICATION ON TRADING TRANSACTION AT PRINGGARATA TRADITIONAL MARKET - Danul Aristiawan (Journal of English Language Teaching and Literature (JELTL), 2023)
Interactions gave various kinds of relationships, one of them was on traders relationship. Buyer and seller was relationship that has been effects in human life. Humans as social beings will always have relationships with each other in order to fulfill their life needs. This relationship will occur if it is based on communication. In this regard, communication plays an important role in human life. But the importance of communication will be felt if humans know what communication actually is and how the delivery process was carried out, so that it takes place effectively. In essence, communication is a process of expression between humans, what expressed, thoughts or feelings to others by using language as a channel. In buyer and seller interaction process, the ability to communicate (communicative competence) which was based on the speaker's cultural system, it can support the success of work in the informal sector. As a means of communication and self-expression, language can affect the thoughts and feelings of other humans, so that with language, a person is able to make other people take responsive actions according to the messages exchanged. Broadly speaking, communication is the process of conveying thoughts, feelings, or messages from one person (communicator) to another (communicant). With the medium of language, a communicator is able to influence the communicant and the message conveyed can be understood according to the meanings contained therein. Communication will be successful if the thoughts conveyed by the seller and the buyer can be understood precisely and equally by both parties. Thus, sellers and buyers are the determinants of communication practices and understanding of the messages communicated.